Pengembangan bahan ajar anyflip berbasis Tri N pada pembelajaran IPAS kelas V Sekolah Dasar - Estiningsih, Yuyun Dwi; Wijayanti, Dwi; Setyawan, Arya Dani; Madyarini, Dyan Desi (Universitas Sarjanawiyata Tamansiswa, 2025)
This research aims to 1) Describe the development design of Anyflip instructional materials based on Tri N for Science and Social Studies (IPAS) learning at Tanjungsari Elementary School, Kebumen; 2) Describe the feasibility level of Anyflip instructional materials based on Tri N for IPAS learning at Tanjungsari Elementary School, Kebumen; 3) Determine students' responses to the use of Anyflip instructional materials based on Tri N for IPAS learning at Tanjungsari Elementary School, Kebumen. This study employs a research and development (R&D) approach and was conducted during the academic year 2023/2024. The development model used is ADDIE, which consists of five stages: Analyze, Design, Develop, Implement, and Evaluate. The instructional media developed is the instructional materials. The subjects of the study were fifth-grade students at Tanjungsari Elementary School, Kebumen. The object of this study was the Anyflip instructional materials based on Tri N. Media feasibility assessment was conducted by media experts and subject matter experts. The instruments used were observation sheets, interview guidelines, validation questionnaires, and student response questionnaires. Data analysis techniques involved qualitative and quantitative analyses. The results indicate that: 1) This study produced Anyflip instructional materials based on TRI N using the ADDIE development steps, namely Analyze, Design, Develop, Implement, and Evaluate; 2) The feasibility level of the Anyflip instructional materials, according to subject matter expert validation, scored 98 and according to media expert validation, scored 77, categorized as very feasible; 3) Student responses showed a positive category and were deemed highly feasible for use in the learning process, with a field trial score of 90%. Therefore, the Anyflip instructional materials based on Tri N, developed using the ADDIE model for fifth-grade IPAS learning, are highly suitable and received positive responses from students.